Mediterranean pine and oak distribution in southern Spain: Is there a mismatch between regeneration and adult distribution? - Urbieta, Itziar R; Garcia, Luis V; Zavala, MIGUEL a; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the current distribution of pine and oak species along environmental gradients in southern Spain? Do pine and oak regeneration niches differ from the environmental niches of adults? Is oak species regeneration favoured under the canopy of pine forests? Location: Forest areas of Andalusia (∼87 600 km2, southern Spain). Methods: We compiled extensive forest inventory data to explore differences in abundance (basal area, m2 ha−1) patterns of adults (dbh >7.4 cm) and regeneration (dbh ≤7.4 cm) of five pine and five oak species. Canonical correspondence analysis (CCA) and generalized linear models were applied to explore species–environment relationships along climatic, edaphic, topographic and fire-frequency gradients. Results: Both pines and oaks segregated along complex environmental gradients, with pines generally dominating in more severe (colder and drier) environments, while oaks dominated in milder, wetter winter areas. In 40-55% of mature pine stands there was a lack of regeneration in the understorey, while in two oak species (Q. suber and Q. canariensis) 70% of stands did not show regeneration. Pine recruits were found at a higher frequency and abundance under the canopy of their congeners, whereas some oaks (Q. ilex) had greater regeneration under mixed pine–oak canopies. Conclusions: Climatic limitations and soil properties partly explained the regional distribution of pines and oaks. We found evidence for an upward shift of Q. ilex recruits towards areas with colder conditions in pine forests, which could be explained by a possible facilitative effect of the pine canopy on seedling establishment.
Keywords: Distribution range; Holm oak; mediterranean forest; Niche expansion; Pinus spp.; Quercus spp.; regeneration dynamics